Caesar, the Germani, and Rome: Ethnography and Politics in the De Bello Gallico - Polito, Roberto (Hyperboreus, 2013)
At the opening of De bello Gallico Caesar gives a description of hostile tribes which is surprisingly positive. They are said to be uncivilized and restless, as we might expect. But he does not judge these characteristics negatively. Rather, he contrasts them favourably with the ‘effeminacy’ of Gaul allies, whom he deems to have been spoiled by contact with Roman civilization. I suggest that this passage and others like it throw light on Caesar’s views concerning society and civilization. Here, in fact, Caesar is using his enemies as a way of reﬂecting on an alternative and more valuable model for Rome itself.